Proteomic exploration reveals a metabolic rerouting due to low oxygen during controlled germination of malting barley (Hordeum vulgare L.) - O'Lone, Clare E.; Juhász, Angéla; Nye-Wood, Mitchell; Dunn, Hugh; Moody, David; Ral, Jean-Philippe; Colgrave, Michelle L. (Frontiers in Plant Science, 2023)
Barley (Hordeum vulgare L.) is used in malt production for brewing applications. Barley malting involves a process of controlled germination that modifies the grain by activating enzymes to solubilize starch and proteins for brewing. Initially, the grain is submerged in water to raise grain moisture, requiring large volumes of water. Achieving grain modification at reduced moisture levels can contribute to the sustainability of malting practices. This study combined proteomics, bioinformatics, and biochemical phenotypic analysis of two malting barley genotypes with observed differences in water uptake and modification efficiency. We sought to reveal the molecular mechanisms at play during controlled germination and explore the roles of protein groups at 24 h intervals across the first 72 h. Overall, 3,485 protein groups were identified with 793 significant differentially abundant (DAP) within and between genotypes, involved in various biological processes, including protein synthesis, carbohydrate metabolism, and hydrolysis. Functional integration into metabolic pathways, such as glycolysis, pyruvate, starch and sucrose metabolism, revealed a metabolic rerouting due to low oxygen enforced by submergence during controlled germination. This SWATH-MS study provides a comprehensive proteome reference, delivering new insights into the molecular mechanisms underlying the impacts of low oxygen during controlled germination. It is concluded that continued efficient modification of malting barley subjected to This is a provisional file, not the final typeset article submergence is largely due to the capacity to reroute energy to maintain vital processes, particularly protein synthesis.